2015
DOI: 10.1007/s13224-014-0648-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Antenatal Breast Milk Expression at Term Pregnancy to Improve Post Natal Lactational Performance

Abstract: Objectives To study the effect of antenatal breast milk expression at term pregnancy and subsequent effect on postnatal lactation performance. Methods A sample size of 200 pregnant women who had completed 37 weeks of gestational period was selected. The sample size was divided equally into study (group 1) and control (group 2). The pregnant women in study (group 1) were advised to gently manually express their breasts at least once daily at any time, preferably during bathing. The remaining women constituted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(32 citation statements)
references
References 10 publications
0
31
1
Order By: Relevance
“…AME was also found to have a beneficial effect on exclusive breast milk feeding in the first 24 hr post birth (aRR 1.15) and during hospitalization (aRR 1.16; Forster et al, ). In addition to these studies, a small RCT conducted among healthy nulliparous and multiparous women in India found that significantly more women randomized to antenatal hand expression of colostrum after 37 weeks established “full lactation” where no “top feed” was required within 6 hr postpartum, as compared with usual care (Lamba, Chopra, & Negi, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AME was also found to have a beneficial effect on exclusive breast milk feeding in the first 24 hr post birth (aRR 1.15) and during hospitalization (aRR 1.16; Forster et al, ). In addition to these studies, a small RCT conducted among healthy nulliparous and multiparous women in India found that significantly more women randomized to antenatal hand expression of colostrum after 37 weeks established “full lactation” where no “top feed” was required within 6 hr postpartum, as compared with usual care (Lamba, Chopra, & Negi, ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these studies, a small RCT conducted among healthy nulliparous and multiparous women in India found that significantly more women randomized to antenatal hand expression of colostrum after 37 weeks established "full lactation" where no "top feed" was required within 6 hr postpartum, as compared with usual care (Lamba, Chopra, & Negi, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In study conducted by Lamba S et al the study group 89 (89 %) of the cases established full lactation within 6 h of delivery, whereas in the control group 72 (72 %) of the cases had established full lactation within 6 h. 10 The difference in both the groups was statistically significant (P <0.05) with regard to time interval from initiation of lactation to full lactation. Findings of these studies are comparable to present study which is suggestive of time interval between initiation of lactation to establishment of lactation in study group being significantly less than control group.…”
Section: Discussionmentioning
confidence: 86%
“…An interesting finding of this study was AME promoted the lactogenesis II, and the time to lactogenesis II was advanced with the increase of AME frequency. Though another study had documented AME shortens the time taken to from initiation to full establishment of lactation, but the relationship between the frequency of AME and lactogenesis II was not been analyzed [16]. The baby sucking on the mother's nipple and effectively removes the milk plays a major role in the lactogenesis II [17].…”
Section: Discussionmentioning
confidence: 99%
“…Women who delayed lactogenesis II are more likely to stop breastfeeding prematurely than that do not. Antenatal milk expression (AME) has been suggested as a potential intervention to address these issues [14][15][16]. AME refers to extracting colostrum from the breast before birth by hand expressing.…”
Section: Introductionmentioning
confidence: 99%